Customer Perceptions of Value: Case of Retail Banking - Ivanauskienė Neringa; Auruškevičienė Viltė; Škudienė, Vida; Nedzinskas, Šarūnas (Organizations and Markets in Emerging Economies, 2012)
Recently, a growing interest in relationship marketing approach attracted much attention of marketers to the customer value creation and delivery as the most important task of marketing strategy. The fact that in the period of economic recession, the retail banking sector customers are more intended to re-assess their relationship with financial organization made marketing experts focus on the investigation of the factors that create and increase customer value in new light. Value creation and delivering to the customer in financial markets has been viewed as a competitive priority and a key component of an organization’s long term success. The aim of the current research paper is to assess the factors of customer perceived value in the retail banking sector during the period of economic recession. The research method involved the survey conducted with 200 retail customers of commercial banks in Lithuania. In addition, this research specifically examines the perception of value in the transitional economy. The study results revealed that in the period of economic recession the dimensions of emotional (affective) value (i.e., the reliability and security of bank, good psychological climate when contacting with bank personnel) and functional value (i.e., the quality of service provision, the competence of contact personnel) are rated higher by customers. Meanwhile, the factors of social value (i.e., the established long-term relationship, personal beliefs, social integration, the opinion and recommendations of relatives, acquaintances and/or friends) are rated lower.